Ilmu Balaqhah Al-Quran, Pengertian Fashahatul Mufrad: Tanafuri Al-Huruf, Gharabah, Mukhalafatul Qiyas - Fauziah Nur Ariza; Muhammad Habib Prasetyo; Edo Dermawan; Mahlil Lubis; Ahmad Taufik Alfarizi Siagian; Muhammad Fajar Ramadhan; Hafiz Ardiansyah (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2025)
Dala’il al-I’jaz is one of the monumental works of ʿAbd al-Qāhir al-Jurjānī, a central figure in the field of balāghah (Arabic rhetoric), widely recognized as one of its foundational scholars. He authored numerous works exploring the intricacies of rhetoric, with Dala’il al-I’jaz serving as a key reference in the study. One of the major themes in balāghah is the concept of al-fasāḥah (eloquence), which serves as the formal object of this research. The focus of this study is to examine al-Jurjānī’s perspective on al-fasāḥah as presented in his work, Dala’il al-I’jaz. This study employs a qualitative descriptive approach by analyzing scholarly articles and relevant literature, with Dala’il al-I’jaz as the main material object. The findings reveal that al-Jurjānī views al-fasāḥah not merely as a matter of wording or phonetic beauty, but rather as something rooted in meaning. In his view, eloquence lies not only in the form or sound of expressions, but more importantly, in the depth and precision of the meaning conveyed.